Adoption behaviour of farmers practicing agroforestry in Jabalpur district (M.P.) in Central India - Sharma, Aashutosh; Agarwal, Rasmi; Upadhayaya, S.D. (Indian Journal of Agroforestry, 2020)
The present paper assesses the adoption behaviour and inter relationship between selected sociopersonal and economic variables of farmers practicing agroforestry in Jabalpur district. Data were collected through exploratory survey of purposively sampled farmers in the seven blocks of Jabalpur district with a pre tested interview schedule. Maximum number of farmers (40%) adopted the practices of agri-silvi-horticultural system, whereas majority of the farmers (48.6%) had low adoption score of agroforestry practices followed by medium (33.1 %) and high (18.3%) adoption score in Jabalpur district. Socio economic variables viz., family size, education, social participation, land holding, household material and socio economic status have positive significant relationship, while age had negative significant correlation only to marginal farmers.